The Role of Financial Market Development in Renewable Energy Generation: Evidence from European Countries - Bonga-Bonga, Lumengo; Kirsten, Frederich (International Journal of Energy Economics and Policy, 2025)
This paper investigates the relationship between renewable energy generation and financial market development in European countries. It enhances the existing literature by analysing this relationship through three dimensions of financial market development—access, efficiency, and depth—and by categorizing renewable energy generation into three types: Wind, solar, and hydroelectric. The study also examines the mediating role of stock market capitalization in this nexus. Employing panel two-stage least squares (2SLS) based on Lewbel’s instrumental variable approach, the findings reveal that wind energy generation is the most responsive to the different components of financial market development in European countries. Furthermore, using bootstrapping causal mediation analysis, the results confirm a significant mediating effect of stock market capitalization, particularly in the influence of financial market development on wind energy generation. These findings provide actionable insights for policymakers aiming to finance renewable energy initiatives to advance Sustainable Development Goal 13.